Analisis Nilai Tambah Nanas Menjadi Keripik Nanas dan Pendapatan Produsen Keripik Nanas: Studi Kasus: Desa Onanrunggu I, Kecamatan Sipahutar Tapanuli Utara - Elisa Sianturi; Rika Fitri Ilvira; Gustami Harahap (Economic Reviews Journal, 2024)
This research analyzes the added value of processing pineapple into pineapple chips in Onanrunggu I Village, Sipahutar District, North Tapanuli. This research uses the Hayami method to calculate added value, which shows that processing pineapple into chips makes a significant contribution to the local economy through job creation and increased income. The data collection method was carried out through in-depth interviews with pineapple chip producers, direct observation of the production process, and analysis of documents related to costs and income. The analytical methods used include calculating added value, profit margins and production efficiency. The analysis results show that the added value from pineapple chips production reaches IDR 11,200 per kilogram with a value added ratio of 75%. The profit margin per kilogram is IDR 1,125 with a profit level of up to 80%. The research results show that the production process involving selecting quality fruit, frying with vacuum frying technology, and attractive packaging has proven to be effective in increasing the economic value of the product. Competitive marketing strategies also play an important role in increasing product competitiveness in the market. This research highlights the importance of innovation in the processing of agricultural products to increase added value and economic welfare of society.